Influence of negative ions on the stoichiometry and structure of carbon nitride films deposited by reactive magnetron sputtering - Wieschhoff, Christian; Theile-Rasche, Chantal; Wang, Fuzeng; Prib, Michael; Moldt, Viktoria Daniela Dorothea; Grundmeier, Guido; Salas, Nieves López; de los Arcos de Pedro, Maria Teresa (Journal of Applied Physics)
Magnetron-sputtered CNx thin films are primarily employed as hard, low-friction protective and tribological coatings, as solar cells, and for catalytic applications. Lower growth rates and a reduced N content, favoring graphitic sp2 structures, hinder industrial scalability due to prolonged deposition times and produce softer, less dense films with inferior hardness, elasticity, and wear resistance. Carbon nitride films deposited by magnetron sputtering exhibit growth behavior strongly influenced by plasma–surface interactions. However, nitrogen resputtering and reduced film growth rates are commonly attributed to chemical etching by positive ions. We propose an additional, unreported power-dependent mechanism involving negative ions formed at the carbon target. These ions are accelerated through the plasma sheath, reaching the substrate with high kinetic energy and inducing both chemical and physical resputtering. This effect is localized to the geometrical projection of the target, as shown by spatially resolved analysis: ellipsometry reveals thickness reduction, and x-ray photoelectron spectroscopy and Raman spectroscopy indicate nitrogen depletion within this region. Correlation between stoichiometry and structural signatures confirms the decisive role of negative ions in modifying the film composition and microstructure. At the same time, the composition of the gas mixture exerts only a minor effect.

Laterally coupled vertical-cavity surface-emitting lasers with tunable resonance width and frequency - Lindemann, M.; D’Alessandro, M.; Ledentsov, N.; Makarov, O. Y.; Ledentsov, N. N.; Tibaldi, A.; Gerhardt, Nils Christopher; Hofmann, M. R. (Journal of Applied Physics)
Laterally coupled vertical-cavity surface-emitting lasers (VCSELs) can exhibit additional resonances at high modulation frequencies that can substantially increase the laser’s modulation bandwidth. State-of-the-art laterally coupled devices require non-standard manufacturing technology and precise tuning of the currents supplied to each cavity separately to form optical supermodes suitable for such resonances. Here, we report on a novel switching phenomenon in laterally coupled VCSEL structures having only a single common electric contact and manufactured in a standard oxide-confined VCSEL geometry. At lower currents, they can be operated in a weakly coupled (WCR) regime and, at higher currents, in an injection-locked (IL) regime, enabling fundamentally different spectral and dynamic features. In the WCR, both optical supermodes lase and a narrow tunable plasma-assisted peak at their beating frequency is observed for each of the apertures, with a current-dependent frequency tuning and anti-phase intensity oscillations in each of the cavities. In contrast, in the IL regimes, only one (anti-symmetric) supermode lases. This adds a broader resonance to the modulation response while the intensity oscillations in both cavities are in-phase. Only the IL regime can result in increased modulation bandwidth of the system. Measurements of the pulse responses and continuous modulation up to 70 GHz for both operational regimes are presented and compared with simulations of our distributed rate equation model whose parameters are extracted from full-wave electromagnetic simulations of the device, including the temperature distribution in the device. Excellent agreement is found and enables comprehensive understanding of the dynamics of supermodes in oxide-confined coupled cavity VCSELs.

Laterally coupled vertical-cavity surface-emitting lasers with tunable resonance width and frequency - Lindemann, M.; D’Alessandro, M.; Ledentsov, N.; Makarov, O. Y.; Ledentsov, N. N.; Tibaldi, A.; Gerhardt, N. C.; Hofmann, M. R. (Journal of Applied Physics)

Second harmonic generation contrasts of ferroelectric domain structures and composition in lithium niobate–tantalate mixed crystals - Koppitz, Boris; Saxena, Tanya; Bernhardt, Felix; Ganschow, Steffen; Sanna, Simone; Rüsing, Michael; Eng, Lukas M. (Journal of Applied Physics)
Lithium niobate–tantalate mixed (LNT) crystals promise improved performance and new applications for optical, piezomechanical, or electrical devices when compared to the end composition compounds lithium niobate and lithium tantalate. The macroscopic properties of ferroelectrics highly depend on the structure of the underlying ferroelectric domains, which within mixed crystals can interact with the local changes in chemical compositions. In this work, we demonstrate how ferroelectric domain walls can unambiguously be identified and distinguished from local changes in composition by correlating piezoresponse force microscopy with second harmonic generation microscopy, using the Cherenkov contrast, reference crystal contrast, and negative phase mismatching contrast. We demonstrate how measuring the associated intensity change when approaching negative phase mismatching can be used to deduce the local tantalum concentration fast and over a large sample area. Based on these results, we study the natural domain structures that appear from Czochralski-grown, multi-domain LNT solid solution crystals. The developed results and methods serve as the central foundation to poling these mixed crystal systems and are key for their integration and applications.

Laterally coupled vertical-cavity surface-emitting lasers with tunable resonance width and frequency - Lindemann, M.; D’Alessandro, M.; Ledentsov, N.; Makarov, O. Y.; Ledentsov, N. N.; Tibaldi, A.; Gerhardt, N. C.; Hofmann, M. R. (Journal of Applied Physics)
Laterally coupled vertical-cavity surface-emitting lasers (VCSELs) can exhibit additional resonances at high modulation frequencies that can substantially increase the laser’s modulation bandwidth. State-of-the-art laterally coupled devices require non-standard manufacturing technology and precise tuning of the currents supplied to each cavity separately to form optical supermodes suitable for such resonances. Here, we report on a novel switching phenomenon in laterally coupled VCSEL structures having only a single common electric contact and manufactured in a standard oxide-confined VCSEL geometry. At lower currents, they can be operated in a weakly coupled (WCR) regime and, at higher currents, in an injection-locked (IL) regime, enabling fundamentally different spectral and dynamic features. In the WCR, both optical supermodes lase and a narrow tunable plasma-assisted peak at their beating frequency is observed for each of the apertures, with a current-dependent frequency tuning and anti-phase intensity oscillations in each of the cavities. In contrast, in the IL regimes, only one (anti-symmetric) supermode lases. This adds a broader resonance to the modulation response while the intensity oscillations in both cavities are in-phase. Only the IL regime can result in increased modulation bandwidth of the system. Measurements of the pulse responses and continuous modulation up to 70 GHz for both operational regimes are presented and compared with simulations of our distributed rate equation model whose parameters are extracted from full-wave electromagnetic simulations of the device, including the temperature distribution in the device. Excellent agreement is found and enables comprehensive understanding of the dynamics of supermodes in oxide-confined coupled cavity VCSELs.

Laterally coupled vertical-cavity surface-emitting lasers with tunable resonance width and frequency - Lindemann, M.; D’Alessandro, M.; Ledentsov, N.; Makarov, O. Y.; Ledentsov, N. N.; Tibaldi, A.; Gerhardt, N. C.; Hofmann, M. R. (Journal of Applied Physics)
Laterally coupled vertical-cavity surface-emitting lasers (VCSELs) can exhibit additional resonances at high modulation frequencies that can substantially increase the laser’s modulation bandwidth. State-of-the-art laterally coupled devices require non-standard manufacturing technology and precise tuning of the currents supplied to each cavity separately to form optical supermodes suitable for such resonances. Here, we report on a novel switching phenomenon in laterally coupled VCSEL structures having only a single common electric contact and manufactured in a standard oxide-confined VCSEL geometry. At lower currents, they can be operated in a weakly coupled (WCR) regime and, at higher currents, in an injection-locked (IL) regime, enabling fundamentally different spectral and dynamic features. In the WCR, both optical supermodes lase and a narrow tunable plasma-assisted peak at their beating frequency is observed for each of the apertures, with a current-dependent frequency tuning and anti-phase intensity oscillations in each of the cavities. In contrast, in the IL regimes, only one (anti-symmetric) supermode lases. This adds a broader resonance to the modulation response while the intensity oscillations in both cavities are in-phase. Only the IL regime can result in increased modulation bandwidth of the system. Measurements of the pulse responses and continuous modulation up to 70 GHz for both operational regimes are presented and compared with simulations of our distributed rate equation model whose parameters are extracted from full-wave electromagnetic simulations of the device, including the temperature distribution in the device. Excellent agreement is found and enables comprehensive understanding of the dynamics of supermodes in oxide-confined coupled cavity VCSELs.

Probing ferroelectric phase transitions in barium titanate single crystals via in-situ second harmonic generation microscopy - Kirbus, Benjamin; Seddon, Samuel D.; Kiseleva, Iuliia; Beyreuther, Elke; Rüsing, Michael; Eng, Lukas M. (Journal of Applied Physics)
Ferroelectric materials play a crucial role in a broad range of technologies due to their unique properties that are deeply connected to the pattern and behavior of their ferroelectric (FE) domains. Chief among them, barium titanate (BaTiO3; BTO) sees widespread applications such as in electronics but equally is a ferroelectric model system for fundamental research, e.g., to study the interplay of such FE domains, the domain walls (DWs), and their macroscopic properties, owed to BTO’s multiple and experimentally accessible phase transitions. Here, we employ Second Harmonic Generation Microscopy (SHGM) to in situ investigate the cubic-to-tetragonal (at ∼126°C) and the tetragonal-to-orthorhombic (at ∼5°C) phase transition in single-crystalline BTO via three-dimensional (3D) DW mapping. We demonstrate that SHGM imaging provides the direct visualization of FE domain switching as well as the domain dynamics in 3D, shedding light on the interplay of the domain structure and phase transition. These results allow us to extract the different transition temperatures locally, to unveil the hysteresis behavior, and to determine the type of phase transition at play (first/second order) from the recorded SHGM data. The capabilities of SHGM in uncovering these crucial phenomena can easily be applied to other ferroelectrics to provide new possibilities for in situ engineering of advanced ferroic devices.

Toward the reproducible fabrication of conductive ferroelectric domain walls into lithium niobate bulk single crystals - Ratzenberger, Julius; Kiseleva, Iuliia; Koppitz, Boris; Beyreuther, Elke; Zahn, Manuel; Gössel, Joshua; Hegarty, Peter A.; Amber, Zeeshan H.; Rüsing, Michael; Eng, Lukas M. (Journal of Applied Physics)
Ferroelectric domain walls (DWs) are promising structures for assembling future nano-electronic circuit elements on a larger scale since reporting domain wall currents of up to 1 mA per single DW. One key requirement hereto is their reproducible manufacturing by gaining preparative control over domain size and domain wall conductivity (DWC). To date, most works on DWC have focused on exploring the fundamental electrical properties of individual DWs within single-shot experiments, with an emphasis on quantifying the origins of DWC. Very few reports exist when it comes to comparing the DWC properties between two separate DWs, and literally nothing exists where issues of reproducibility in DWC devices have been addressed. To fill this gap while facing the challenge of finding guidelines for achieving predictable DWC performance, we report on a procedure that allows us to reproducibly prepare single hexagonal domains of a predefined diameter into uniaxial ferroelectric lithium niobate single crystals of 200 and 300 μm thickness, respectively. We show that the domain diameter can be controlled with an uncertainty of a few percent. As-grown DWs are then subjected to a standard procedure of current-limited high-voltage DWC enhancement, and they repetitively reach a DWC increase of six orders of magnitude. While all resulting DWs show significantly enhanced DWC values, their individual current–voltage (I–V) characteristics exhibit different shapes, which can be explained by variations in their 3D real structure reflecting local heterogeneities by defects, DW pinning, and surface-near DW inclination.

Depth resolution in piezoresponse force microscopy - Roeper, Matthias; Seddon, Samuel D.; Amber, Zeeshan H.; Rüsing, Michael; Eng, Lukas M. (Journal of Applied Physics)
Piezoresponse force microscopy (PFM) is one of the most widespread methods for investigating and visualizing ferroelectric domain structures down to the nanometer length scale. PFM makes use of the direct coupling of the piezoelectric response to the crystal lattice, and hence, it is most often applied to spatially map the three-dimensional (3D) near-surface domain distribution of any polar or ferroic sample. Nonetheless, since most samples investigated by PFM are at least semiconducting or fully insulating, the electric ac field emerging from the conductive scanning force microscopy (SFM) tip penetrates the sample and, hence, may also couple to polar features that are deeply buried into the bulk of the sample under investigation. Thus, in the work presented here, we experimentally and theoretically explore the contrast and depth resolution capabilities of PFM, by analyzing the dependence of several key parameters. These key parameters include the depth of the buried feature, i.e., here a domain wall (DW), as well as PFM-relevant technical parameters such as the tip radius, the PFM drive voltage and frequency, and the signal-to-noise ratio. The theoretical predictions are experimentally verified using x-cut periodically poled lithium niobate single crystals that are specially prepared into wedge-shaped samples, in order to allow the buried feature, here the DW, to be “positioned” at any depth into the bulk. This inspection essentially contributes to the fundamental understanding in PFM contrast analysis and to the reconstruction of 3D domain structures down to a 1 μm-penetration depth into the sample.
Keywords: Ferroelectrics; lithium niobate; piezoresponse force microscopy

Modeling nonlinear optical interactions of focused beams in bulk crystals and thin films: A phenomenological approach - Spychala, Kai J.; Amber, Zeeshan H.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Coherent nonlinear optical μ-spectroscopy is a frequently used tool in modern material science as it is sensitive to many different local observables, which comprise, among others, crystal symmetry and vibrational properties. The richness in information, however, may come with challenges in data interpretation, as one has to disentangle the many different effects like multiple reflections, phase jumps at interfaces, or the influence of the Guoy-phase. In order to facilitate interpretation, the work presented here proposes an easy-to-use semi-analytical modeling Ansatz, which bases upon known analytical solutions using Gaussian beams. Specifically, we apply this Ansatz to compute nonlinear optical responses of (thin film) optical materials. We try to conserve the meaning of intuitive parameters like the Gouy-phase and the nonlinear coherent interaction length. In particular, the concept of coherence length is extended, which is a must when using focal beams. The model is subsequently applied to exemplary cases of second- and third-harmonic generation. We observe a very good agreement with experimental data, and furthermore, despite the constraints and limits of the analytical Ansatz, our model performs similarly well as when using more rigorous simulations. However, it outperforms the latter in terms of computational power, requiring more than three orders less computational time and less performant computer systems.
Keywords: General Physics and Astronomy

Time-resolved pump–probe spectroscopic ellipsometry of cubic GaN. I. Determination of the dielectric function - Baron, Elias; Goldhahn, Rüdiger; Espinoza, Shirly; Zahradník, Martin; Rebarz, Mateusz; Andreasson, Jakob; Deppe, Michael; As, Donat Josef; Feneberg, Martin (Journal of Applied Physics)
An ultra-fast change of the absorption onset for zincblende gallium-nitride (zb-GaN) (fundamental bandgap: 3.23 eV) is observed by investigating the imaginary part of the dielectric function using time-dependent femtosecond pump–probe spectroscopic ellipsometry between 2.9 and 3.7 eV. The 266 nm (4.66 eV) pump pulses induce a large electron–hole pair concentration up to 4×1020cm−3, which shift the transition energy between conduction and valence bands due to many-body effects up to ≈500 meV. Here, the absorption onset increases due to band filling while the bandgap renormalization at the same time decreases the bandgap. Additionally, the absorption of the pump-beam creates a free-carrier profile within the 605 nm zb-GaN layer with high free-carrier concentrations at the surface, and low concentrations at the interface to the substrate. This leads to varying optical properties from the sample surface (high transition energy) to substrate (low transition energy), which are taken into account by grading analysis for an accurate description of the experimental data. For this, a model describing the time- and position-dependent free-carrier concentration is formulated by considering the relaxation, recombination, and diffusion of those carriers. We provide a quantitative analysis of optical experimental data (ellipsometric angles Ψ and Δ) as well as a plot for the time-dependent change of the imaginary part of the dielectric function.
Keywords: General Physics and Astronomy

14N Hyperfine and nuclear interactions of axial and basal NV centers in 4H-SiC: A high frequency (94 GHz) ENDOR study - Murzakhanov, F. F.; Sadovnikova, M. A.; Mamin, G. V.; Nagalyuk, S. S.; von Bardeleben, H. J.; Schmidt, Wolf Gero; Biktagirov, Timur; Gerstmann, Uwe; Soltamov, V. A. (Journal of Applied Physics)
The nitrogen-vacancy (NV) centers (NCVSi)− in 4H silicon carbide (SiC) constitute an ensemble of spin S = 1 solid state qubits interacting with the surrounding 14N and 29Si nuclei. As quantum applications based on a polarization transfer from the electron spin to the nuclei require the knowledge of the electron–nuclear interaction parameters, we have used high-frequency (94 GHz) electron–nuclear double resonance spectroscopy combined with first-principles density functional theory to investigate the hyperfine and nuclear quadrupole interactions of the basal and axial NV centers. We observed that the four inequivalent NV configurations (hk, kh, hh, and kk) exhibit different electron–nuclear interaction parameters, suggesting that each NV center may act as a separate optically addressable qubit. Finally, we rationalized the observed differences in terms of distinctions in the local atomic structures of the NV configurations. Thus, our results provide the basic knowledge for an extension of quantum protocols involving the 14N nuclear spin.

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Turn all the lights off: Bright- and dark-field second-harmonic microscopy to select contrast mechanisms for ferroelectric domain walls - Hegarty, Peter A.; Beccard, Henrik; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Recent analyses by polarization resolved second-harmonic (SH) microscopy have demonstrated that ferroelectric (FE) domain walls (DWs) can possess non-Ising wall characteristics and topological nature. These analyses rely on locally analyzing the properties, directionality, and magnitude of the second-order nonlinear tensor. However, when inspecting FE DWs with SH microscopy, a manifold of different effects may contribute to the observed signal difference between domains and DWs, i.e., far-field interference, Čerenkov-type phase-matching (CSHG), and changes in the aforementioned local nonlinear optical properties. They all might be present at the same time and, therefore, require careful interpretation and separation. In this work, we demonstrate how the particularly strong Čerenkov-type contrast can selectively be blocked using dark- and bright-field SH microscopy. Based on this approach, we show that other contrast mechanisms emerge that were previously overlayed by CSHG but can now be readily selected through the appropriate experimental geometry. Using the methods presented, we show that the strength of the CSHG contrast compared to the other mechanisms is approximately 22 times higher. This work lays the foundation for the in-depth analysis of FE DW topologies by SH microscopy.
Keywords: General Physics and Astronomy

Nonlinear optical interactions in focused beams and nanosized structures - Amber, Zeeshan H.; Spychala, Kai J.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film materials from μm thickness down to single-atomic-layered 2D materials play a central role in many novel electronic and optical applications. Coherent, nonlinear optical (NLO) μ-spectroscopy offers insight into the local thickness, stacking order, symmetry, or electronic and vibrational properties. Thin films and 2D materials are usually supported on multi-layered substrates leading to (multi-)reflections, interference, or phase jumps at interfaces during μ-spectroscopy, which all can make the interpretation of experiments particularly challenging. The disentanglement of the influence parameters can be achieved via rigorous theoretical analysis. In this work, we compare two self-developed modeling approaches, a semi-analytical and a fully vectorial model, to experiments carried out in thin-film geometry for two archetypal NLO processes, second-harmonic and third-harmonic generation. In particular, we demonstrate that thin-film interference and phase matching do heavily influence the signal strength. Furthermore, we work out key differences between three and four photon processes, such as the role of the Gouy-phase shift and the focal position. Last, we can show that a relatively simple semi-analytical model, despite its limitations, is able to accurately describe experiments at a significantly lower computational cost as compared to a full vectorial modeling. This study lays the groundwork for performing quantitative NLO μ-spectroscopy on thin films and 2D materials, as it identifies and quantifies the impact of the corresponding sample and setup parameters on the NLO signal, in order to distinguish them from genuine material properties.<
Keywords: General Physics and Astronomy

Tuning the Čerenkov second harmonic contrast from ferroelectric domain walls via anomalous dispersion - Hegarty, Peter A.; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Second harmonic (SH) microscopy represents a powerful tool for the investigation of crystalline systems, such as ferroelectrics and their domain walls (DWs). Under the condition of normal dispersion, i.e., the refractive index at the SH wavelength is larger as compared to the refractive index at the fundamental wavelength, n(2ω)>n(ω), bulk crystals will generate no SH signal. Should the bulk, however, contain DWs, an appreciable SH signal will still be detectable at the location of DWs stemming from the Čerenkov mechanism. In this work, we demonstrate both how SH signals are generated in bulk media and how the Čerenkov mechanism can be inhibited by using anomalous dispersion, i.e., n(ω)<n(2ω). This allows us to quantitatively estimate the relative strength of the Čerenkov compared to other SH contrast mechanisms in DWs, such as the interference contrast. The results are in agreement with previous experiments based on the geometric separation of the signals. Due to the observed, strong Čerenkov contrast, such signal contributions may not be neglected in polarimetry studies of ferroelectric DWs in the future.
Keywords: General Physics and Astronomy

Quantifying the coherent interaction length of second-harmonic microscopy in lithium niobate confined nanostructures - Amber, Zeeshan H.; Kirbus, Benjamin; Eng, Lukas M.; Rüsing, Michael (Journal of Applied Physics)
Thin-film lithium niobate (TFLN) in the form of x- or z-cut lithium-niobate-on-insulator has attracted considerable interest as a very promising and novel platform for developing integrated optoelectronic (nano)devices and exploring fundamental research. Here, we investigate the coherent interaction length lc of optical second-harmonic generation (SHG) microscopy in such samples, that are purposely prepared into a wedge shape, in order to elegantly tune the geometrical confinement from bulk thicknesses down to approximately 50 nm. SHG microscopy is a very powerful and non-invasive tool for the investigation of structural properties in the biological and solid-state sciences, especially for visualizing and analyzing ferroelectric domains and domain walls. However, unlike in bulk lithium niobate (LN), SHG microscopy in TFLN is impacted by interfacial reflections and resonant enhancement, both of which rely on film thickness and substrate material. In this paper, we show that the dominant SHG contribution measured on TFLN in backreflection is the co-propagating phase-matched SHG signal and not the counter-propagating SHG portion as is the case for bulk LN samples. Moreover, lc depends on the incident pump laser wavelength (sample dispersion) but also on the numerical aperture of the focussing objective in use. These experimental findings on x- and z-cut TFLN are excellently backed up by our advanced numerical simulations.
Keywords: General Physics and Astronomy

Robust ferroelectric polarization retention in harsh environments through engineered domain wall pinning - Zhang, Dawei; Sando, Daniel; Pan, Ying; Sharma, Pankaj; Seidel, Jan (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Spatially resolved light field analysis of the second-harmonic signal of χ(2)-materials in the tight focusing regime - Spychala, K. J.; Mackwitz, P.; Widhalm, A.; Berth, G.; Zrenner, A. (Journal of Applied Physics)

Spatially resolved light field analysis of the second-harmonic signal of χ(2)-materials in the tight focusing regime - Spychala, K. J.; Mackwitz, P.; Widhalm, A.; Berth, Gerhard; Zrenner, Artur (Journal of Applied Physics)